Building Economic Brand Value through Brand Experience and Engagement: The Mediating Role of Brand Trust on Loyalty among NPURE Consumers - Wati, Sri Sulistiya; Sudarmiatin, Sudarmiatin; Murwani, F. Danardana (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to explore how brand experience and customer brand engagement contribute to the formation of brand loyalty and, ultimately, to the economic value of the brand, with brand trust serving as a mediating variable. The research focuses on users of NPURE skincare products within the PURE FRIENDS community on WhatsApp. Using a quantitative approach, data were collected through an online questionnaire, with a total of 159 respondents selected through purposive sampling. The sample size was determined using an online sample size calculator (calculator.net). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that brand experience has a positive and significant effect on brand loyalty, mediated by brand trust. Although customer brand engagement does not directly influence brand loyalty significantly, brand trust plays a mediating role in strengthening this relationship. These results suggest that enhancing brand experience and engagement—supported by strong brand trust—can contribute to building not only brand loyalty but also long-term economic brand value.